Sequencing and analysis of the complete mitochondrial genome of Blarinella griselda from China and its phylogenetic analysis - Zhu, Liu (Mitochondrial DNA B Resour, 2020)
The complete mitogenome sequence of Blarinella griselda was determined using long PCR. The genome was 16,947 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, 1 origin of L strand replication and 1 control region. The overall base composition of the heavy strand is A (33.1%), C (22.6%), T (31.6%) and G (12.7%). The base compositions present clearly the A–T skew, which is most obviously in the control region and protein-coding genes. Mitochondrial genome analyses based on MP, ML, NJ and Bayesian analyses yielded identical phylogenetic trees. This study verifies the evolutionary status of Blarinella griselda in Soricidae at the molecular level. The mitochondrial genome would be a significant supplement for the Blarinella griselda genetic background. The three Blarinella species formed a monophyletic group with the high bootstrap value (100%) in all examinations.